1991
DOI: 10.1029/91gl02090
|View full text |Cite
|
Sign up to set email alerts
|

The thickness of the magnetosheath: Constraints on the polytropic index

Abstract: A statistical analysis of 351 independent bow shock crossings and 233 independent magnetopause crossings by the ISEE‐I spacecraft from 1977 to 1980 was performed to determine the average positions and shapes of the bow shock and magnetopause. The standoff distance between the magnetopause and the bow shock depends on the compressibility of the plasma which in the ‘polytropic’ approximation is related to the ratio of specific heats, γ. Standoff distances for the bow shock and magnetopause were found to be 13.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
219
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(229 citation statements)
references
References 12 publications
10
219
0
Order By: Relevance
“…The computations based on Slavin and Holzer (1981); Farris et al (1991) led to similar results. The horizontal dashed line corresponds to the critical value of θ c Bn =39.9 • .…”
Section: Local Bow Shock Geometrysupporting
confidence: 68%
See 2 more Smart Citations
“…The computations based on Slavin and Holzer (1981); Farris et al (1991) led to similar results. The horizontal dashed line corresponds to the critical value of θ c Bn =39.9 • .…”
Section: Local Bow Shock Geometrysupporting
confidence: 68%
“…Another model by Cairns et al (1995) emphasizes the MHD effects at low Mach numbers. Finally, a gas dynamics-based model using 351 independent bow shock crossings by the ISEE-1 spacecraft has been reported by Farris et al (1991). They found that these data fit a hyperboloid shape well.…”
Section: Shock Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The different orientation of IMF can affect the fast magnetosonic Mach number. If the waves at the nose of the magnetopause propagate in the radial direction, their fast magnetosonic Mach number will increase under the radial IMF condition, and consequently reducing the standoff distance of the bow shock and then the thickness of the magnetosheath [Farris et al, 1991]. For this reason, MHD modelers should use actual solar wind conditions in global simulations of radial IMF events.…”
Section: Discussionmentioning
confidence: 99%
“…The preceding parameters resulted in an estimation of Alfvén Mach number of M a = 3.7. The Farris shock model surface (Farris et al, 1991) was used to determine the shock normal direction ofn = [0.99, 0.09, −0.03]. The projection of the magnetic field alongn can be seen in the top panel of Fig.…”
Section: Datasets and Instrumentationmentioning
confidence: 99%